Causes of Maritime Disputes in Light of the 1982 United Nations Convention on the Law of the Sea - Sultan bin Mohammed Al-Malki (International Journal of Law Research and Studies, 2025)
The research aims to study maritime disputes in light of the 1982 United Nations Convention on the Law of the Sea and to identify the main causes leading to such disputes. Using a descriptive-analytical approach, the study examines the origins of the Law of the Sea, the precursors to the 1982 Convention, and the conferences that preceded it. Additionally, it explores international disputes, maritime international disputes, and the causes of maritime conflicts. This study has reached several key findings, the most important of which is that maritime disputes receive significant attention from the international community, particularly regarding their resolution and the reduction of their causes. International and maritime courts, in particular, have established specialized chambers to handle specific disputes based on their subject matter, with highly qualified and specialized judges overseeing them. Furthermore, the causes of maritime disputes are not solely due to violations of the 1982 United Nations Convention on the Law of the Sea but may also result from incorrect application or misinterpretation of a bilateral agreement between two states concerning maritime matters. Many maritime disputes share similar causes. The study concludes with several recommendations, the most important being that national legislations should be fully aligned with the 1982 United Nations Convention on the Law of the Sea and its provisions to minimize the emergence of maritime disputes. This would prevent states from acting in violation of the Convention while relying on their domestic laws as justification. Additionally, a comprehensive study of maritime disputes brought before international courts should be conducted to develop a model for resolving such conflicts, serving as a guiding framework for states to expedite dispute resolution.